A flexible unit maintenance scheduling considering uncertainties. - Rong-Ceng Leou (IEEE Transactions on power systems)
This paper presents a new methodology for maintenance scheduling that takes into account the uncertain constraints of the unit maintenance problem. If the spinning reserve is enough, this model can obtain an optimal solution based on reliability or cost concerned. Since the power development is more difficult than ever before, scheduling the unit maintenance under tight spinning reserve is a difficult task. In such a situation, treating various constraints, such as the spinning reserve, duration of maintenance, the maintenance crew, etc., as soft constraints, a fuzzy 0-1 integer programming model is adopted to find the minimum violation solution. In order to verify that this model can be implemented in the real system, a case study of the Taiwan Power System is carried out using the algorithm